Comparative assessment of difficulty scales for removal of the third molar of the lower jaw depending on its position - Gudarian, O.O.; Nekhanevych, Zh.M.; Kycherenko, T.O.; Shepelya, A.V. (Medicni Perspektivi, 2024)
Retention (delayed eruption) of the third molar is one of the most common pathologies in the outpatient practice of a dentist-surgeon. Such a pathology can very often be complicated by inflammatory diseases, such as pericoronitis, periostitis and other more serious diseases. Therefore, early warning and most gentle removal of the causative tooth determines the professionalism of the dental surgeon. A large number of indexes of difficulty of removal of the third molar have been proposed by different authors, but none of them is considered universal and optimal for different clinical cases. The level of complexity is most clearly characterized by a scale that takes into account not only radiological but also clinical and demographic indicators. Such scales exist in modification or in more recent literary sources. Having chosen the most clear and correct scale, it is possible for the surgeon to clearly assess the entire level of complexity and responsibility for surgical intervention on removing the third molar, thereby obtaining the most effective result, minimizing complications both during the operation and after a while. The purpose of the study: justification of the selection of the difficulty rating scale for the removal of the third molar of the lower jaw, depending on its position. The study analyzed and compared 18 basic scales of complexity that are most often used by surgeons before removing the impacted third molar of the lower jaw. Data sources that were used for the search were taken from Medline, PubMed, Google Scholar, Minerva library databases. Each of the difficulty scales was presented and translated into Ukrainian for convenient use in the practice of a dental surgeon. A general table was provided where a comparative analysis of the difficulty scales was made according to thirty parameters. It is shown that the Cosme Gay-Escoda C. scale has the most indicators for preoperative assessment of complexity. There are many difficulty scales for preoperative assessment for the removal of impacted third molars of the lower jaw. Some of them have radiological evaluation criteria, some have clinical criteria, and only the Pernumbuco index (2017), Zhang X. (2019), and Cosme Gay-Escoda C. (2022) scales also have demographic indicators. However, the latter has the largest number of criteria, according to which the difficulty of removing the third molar of the lower jaw is calculated.